Optimalisasi Penerimaan Retribusi Pelayanan Persampahan sebagai Pendapatan Asli Daerah di Kabupaten Sidenreng Rappang - Vebriyanto Vebriyanto (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
This study aims to determine the management of waste retribution in Sidenreng Rappang Regency, along with all influencing factors, and the extent to contribute Sidenreng Rappang Regions’ Original Income. To achieve this, the research was carried out by using a survey method for distributing questionnaires, observations and interviews. The population took 68 people and all of them were accounted as samples. The results showed that although the optimization of waste retribution as regions original income was already quite optimal, but from the staff, management, and all related elements’ side still required an improvement and minimize the affecting factors, such as the competence of all personnel, retribution mandatory which greatly affected the waste management, and facilities and infrastructure improvement to support increasing income curve, it can be seen from the 64.70% of respondents stated quite optimal, and the achievement of roughly 75% of the targets set by the local government, so it can be concluded a quite number of contribution